Sistem Informasi Georgrafis Angka Kematian Ibu dalam Upaya Surveilans Kesehatan di Kabupaten Bondowoso - Jannah, Siti Elatul; Muna, Niyalatul; Rachmawati, Ervina; Roziqin, Mochammad Choirur (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Maternal Mortality Rate (MMR) refers to the death of women during pregnancy or within 42 days after delivery, caused by pregnancy-related conditions or management, excluding accidents. In 2022, Bondowoso Regency ranked 8th in East Java for MMR. By May 2024, the maternal death toll in Bondowoso reached 11, an increase from 10 deaths in 2023. This highlights the need for heightened public awareness regarding maternal mortality. This study aims to create a digital map of MMR distribution. The system development method used is the Waterfall model, utilizing Leaflet for mapping and MySQL as the database. System testing was conducted using the black box method, which confirmed that the system met user requirements. The study produced a web-based system capable of displaying a map of maternal mortality distribution categorized by risk groups, calculated using the maternal mortality formula. The system also provides graphs, report tables easily updated by administrators, and displays distances between cases and hospitals. This Geographic Information System is expected to assist health officers in promoting integrated health programs and educating the public to prevent maternal mortality in Bondowoso Regency.